Characterization of Growth Behavior and the Resulting Forces Applied by Pollen Tubes in a 3D Matrix - Reimann, Ronny; Kah, Delf-Thorge Eric (Pollen and Pollen Tube Biology, 2020)
The question of how pollen tubes orient themselves on their way to the egg cell is a major focus of plant reproduction research. The role of physical guidance through the tissues of the pistil in relation to the mechanical perception and growth adaptation of the pollen tubes has not been sufficiently investigated. In order to advance research on the mechanical perception of pollen tubes and their force application during invasive growth, we present simple methods for the observation and mechanical characterization of pollen tubes in vitro, which can be established with little effort in any biological laboratory with standard equipment. Pollen grains are germinated in a hydrogel containing agarose and their growth is recorded in 3D using brightfield microscopy. Using suitable analysis software, parameters such as growth rate and pollen tube diameter can then be determined to estimate the exerted penetration force.
CRIS-Team Scopus Importer:2020-06-23
Keywords: 3D matrix; Agarose; ClickPoints; Force measurement; Hydrogel; Indentation; Mechanical guidance; Microindenter; Polar growth; Pollen tube; Single cell

Classification of dead and living microalgae Chlorella vulgaris by bioimage informatics and machine learning - Reimann, Ronny; Zeng, Bo; Jakopec, Martin; Burdukiewicz, Michał; Petrick, Ingolf; Schierack, Peter; Rödiger, Stefan (Algal Research, 2020)
The ratio between living and dead cells is an important parameter in microalgae culture and environmental monitoring. Fast, robust and automated analytical methods for monitoring microalgae growth for biotechnological and pharmaceutical applications and for optimizing production strains are needed. We developed a pipeline for the automatic binary classification of living and dead microalgae. We compared multispectral fluorescence microscopy and flow cytometry as readout platforms. Images of Chlorella vulgaris suspension cultures were captured and features of microalgaes (e.g., size) were extracted by bioimage informatics. We classified the microalgae cells with seven machine learning algorithms, including Naive Bayes, Random Forest and Neural Networks. Random Forest was a particularly suitable method for classifying the living/dead microalgae population, the label-free classifier can reach 86% of the area under the curve (AUC) if only morphological characteristics are used. The AUC rose to 99.6% if the fluorescence signal of Syto 9 (dye for all cells) and Propidium iodide (dye for damaged cells) were added as features, and the prediction accuracy reached 96.6% which is over the accuracy of 95% from the cell viability analysis using the staining method. This means that our classifier is useful as it improves the staining method by correcting 30% of the false positive/negative cells. Instead of only predicting single cells, we developed a Random Forest model to classify the distribution of living and dead microalgae populations using the fingerprint vector features, which gives an overall AUC of 94.5% and accuracy of 82%. We found that dead cells are significantly larger in average diameter (1.4-fold, p < 0.01) and area (1.5-fold, p < 0.01) when compared to living cells. In summary, combinations of statistical methods, bioimage informatics and machine learning are useful approaches for automated investigation in analyzing population dynamics of microalgae cultures.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Bioimage informatics; Chlorella vulgaris; Flow cytometry; Fluorescence microscopy; Machine learning; Microalgae

Durotropic Growth of Pollen Tubes(1)([OPEN]) - Reimann, Ronny; Kah, Delf-Thorge Eric; Mark, Christoph; Dettmer, Jan; Reimann, Theresa; Gerum, Richard; Geitmann, Anja; Fabry, Ben; Dietrich, Petra; Kost, Benedikt (Plant Physiology, 2020)
To reach the female gametophyte, growing pollen tubes must penetrate different tissues within the pistil, the female reproductive organ of a flower. Past research has identified various chemotropic cues that guide pollen tubes through the transmitting tract of the pistil, which represents the longest segment of its growth path. In addition, physical mechanisms also play a role in pollen tube guidance; however, these processes remain poorly understood. Here we show that pollen tubes from plants with solid transmitting tracts actively respond to the stiffness of the environment. We found that pollen tubes fromNicotiana tabacumand other plant species with a solid or semisolid transmitting tract increase their growth rate in response to an increasing matrix stiffness. By contrast, pollen tubes fromLilium longiflorumand other plant species with a hollow transmitting tract decrease their growth rate with increasing matrix stiffness, even though the forces needed to maintain a constant growth rate remain far below the maximum penetration force these pollen tubes are able to generate. Moreover, when confronted with a transition from a softer to a stiffer matrix, pollen tubes fromN. tabacumdisplay a greater ability to penetrate into a stiffer matrix compared with pollen tubes fromL. longiflorum,even though the maximum force generated by pollen tubes fromN. tabacum(11 mu N) is smaller than the maximum force generated by pollen tubes fromL. longiflorum(36 mu N). These findings demonstrate a mechano-sensitive growth behavior, termed here durotropic growth, that is only expressed in pollen tubes from plants with a solid or semisolid transmitting tract and thus may contribute to an effective pollen tube guidance within the pistil.
CRIS-Team WoS Importer:2020-07-10

Durotropic Growth of Pollen Tubes - Reimann, Ronny; Kah, Delf-Thorge Eric; Mark, Christoph; Dettmer, Jan; Reimann, Theresa; Gerum, Richard; Geitmann, Anja; Fabry, Ben; Dietrich, Petra; Kost, Benedikt (Plant Physiology, 2020)
To reach the female gametophyte, growing pollen tubes must penetrate different tissues within the pistil, the female reproductive organ of a flower. Past research has identified various chemotropic cues that guide pollen tubes through the transmitting tract of the pistil, which represents the longest segment of its growth path. In addition, physical mechanisms also play a role in pollen tube guidance; however, these processes remain poorly understood. Here we show that pollen tubes from plants with solid transmitting tracts actively respond to the stiffness of the environment. We found that pollen tubes from Nicotiana tabacum and other plant species with a solid or semisolid transmitting tract increase their growth rate in response to an increasing matrix stiffness. By contrast, pollen tubes from Lilium longiflorum and other plant species with a hollow transmitting tract decrease their growth rate with increasing matrix stiffness, even though the forces needed to maintain a constant growth rate remain far below the maximum penetration force these pollen tubes are able to generate. Moreover, when confronted with a transition from a softer to a stiffer matrix, pollen tubes from N. tabacum display a greater ability to penetrate into a stiffer matrix compared with pollen tubes from L. longiflorum, even though the maximum force generated by pollen tubes from N. tabacum (11 µN) is smaller than the maximum force generated by pollen tubes from L. longiflorum (36 µN). These findings demonstrate a mechano-sensitive growth behavior, termed here durotropic growth, that is only expressed in pollen tubes from plants with a solid or semisolid transmitting tract and thus may contribute to an effective pollen tube guidance within the pistil. Animal sperm cells have the ability to freely swim by rhythmic movements of their flagella (Malo et al., 2006). By contrast, sperm cells of angiosperm plants have lost this ability (Dresselhaus et al., 2016) and are contained within the cytoplasm of the vegetative cell of a pollen grain. Upon germination, the vegetative pollen cell forms a long tubular protrusion, the pollen tube, which rapidly elongates through the pistil and transports the enclosed immobile sperm cells toward the egg cell and the central cell for double fertilization (Zhang et al., 2017). As opposed to cell division, pollen tubes elongate by tip growth. This process depends on a fine-tuned interplay between turgor pressure and vesicle trafficking, which delivers material required for cell wall and plasma membrane extension exclusively to the pollen tube tip (Lord, 2000; Chebli et al., 2013; Hafidh et al., 2016a; Grebnev et al., 2017; Luo et al., 2017). Therefore, only the surface at the pollen tube tip changes its relative position with respect to the environment during cell elongation, giving rise to a low-friction and thus energetically favorable growth process that has also been observed in other invasively growing cell types, such as root hairs, fungal hyphae, and neurons (Palanivelu and Preuss, 2000; Sanati Nezhad and Geitmann, 2013). This mechanism enables pollen tubes of some plant species to grow at rates of more than 300 µm·min−1 (Williams et al., 2016), faster than any other plant cell (Shamsudhin et al., 2016). To reach the female gametophyte, growing pollen tubes must penetrate different tissues within the pistil. After initial growth on the surface of the stigma, pollen tubes subsequently elongate through the transmitting tract within the style and the ovary, penetrate the septum epidermis to leave the transmitting tract, continue to elongate on the surface of the funiculus and through the micropyle of the ovule, and finally enter a synergid cell, where they burst and discharge their cytoplasm together with the enclosed sperm cells (Hulskamp et al., 1995; Crawford et al., 2007). Over the past two decades, many factors have been identified that are involved in the guidance of pollen tubes along their path toward the female gametophyte, including sugars, calcium ions, nitric oxide, lipids, and secreted peptides (Hulskamp et al., 1995; Ray et al., 1997; Wolters-Arts et al., 1998; Mollet et al., 2000; Higashiyama et al., 2003; Prado et al., 2004; Chae and Lord, 2011; Sanati Nezhad et al., 2014; Qu et al., 2015; Hafidh et al., 2016b; Higashiyama and Yang, 2017; Jiao et al., 2017). Most of these chemical signals guide the pollen tubes toward and inside the ovule following their emergence from the transmitting tract. However, the transmitting tract of the pistil typically represents the longest section of the pollen tube growth path in situ (de Graaf et al., 2003; Crawford and Yanofsky, 2008). Because chemical gradients are more difficult to maintain over longer distances, physical guidance mechanisms are thought to play an important role in directing pollen tube growth within the transmitting tract (Lennon et al., 1998; Lush et al., 2000), but this has so far not been characterized in detail. Flowers of different plant species display a highly diverse pistil and transmitting tract anatomy, which complicates the investigation of physical pollen tube guidance. Within the transmitting tract of hollow (sometimes called “open”) styles, as observed for example in Lilium longiflorum flowers, pollen tubes grow on the epidermal surface of a cell-free canal filled with a viscous extracellular matrix (Sanders and Lord, 1992; de Graaf et al., 2001; Erbar, 2003). By contrast, the transmitting tract in solid (sometimes called “closed”) styles, as found in Arabidopsis (Arabidopsis thaliana) and Nicotiana tabacum flowers, is filled with tissue composed of cells embedded in an extracellular matrix, which pollen tubes need to penetrate (Lennon et al., 1998; Cheung et al., 2000; Erbar, 2003). The tissue within the transmitting tract imposes a substantial physical resistance on pollen tube growth (Agudelo et al., 2012), in particular as intercellular spaces in this tissue are typically smaller than the pollen tube diameter (Lennon et al., 1998; Roy et al., 1999; Cheung et al., 2000). The maximum (or stalling) force that a growing pollen tube can generate to overcome the mechanical resistance restricting its expansion within pistil tissues is determined by the product of the hydrostatic turgor pressure and the cross-sectional area of the tube at its tip. Maximum forces generated by L. longiflorum tubes measured with capacitive force sensors (Burri et al., 2018) were found to be in the range of 9.6 ± 1.6 µN, whereas forces generated by Camellia japonica pollen tubes measured with soft microcantilevers (Ghanbari et al., 2018) were found to be around 1.5 µN. However, direct force measurements using capacitive force sensors or microcantilevers are technically highly demanding (Agudelo et al., 2013; Ghanbari et al., 2014; Sanati Nezhad et al., 2014). Moreover, measurements of the maximum stalling force cannot provide information on the penetration force of a pollen tube growing inside a pistil under physiological conditions, as this force depends on the growth rate and the mechanical impedance of the surrounding matrix (Sanati Nezhad et al., 2013). In this study, we present a method to estimate the penetration force generated by a pollen tube tip during its growth through matrices of different stiffness. With this method, we investigated pollen tubes from plant species, both with hollow and with solid styles, and measured the relationship between penetration force and growth rate for matrices with different mechanical properties. We found that pollen tubes from plants with solid styles, but not those from plants with hollow styles, increase their growth rate in matrices with higher physical resistance, indicating that an active mechanosensory mechanism controls the tropic growth of these pollen tubes, which may help them to navigate through the complex architecture of the pistil to reach the female gametophyte. We propose the term durotropism for this mechanosensory mechanism that guides pollen tubes from plants with solid styles toward stiffer environments, analogous to the term durotaxis that describes the preferential migration of mammalian mesenchymal cells toward regions with higher substrate rigidity (Lo et al., 2000

Multiple cyclic nucleotide-gated channels coordinate calcium oscillations and polar growth of root hairs - Brost, Christa; Studtrucker, Tanja; Reimann, Ronny; Denninger, Philipp; Czekalla, Jennifer; Krebs, Melanie; Fabry, Ben; Schumacher, Karin; Grossmann, Guido; Dietrich, Petra (Plant Journal, 2019)
Calcium gradients underlie polarization in eukaryotic cells. In plants, a tip-focused Ca2+-gradient is fundamental for rapid and unidirectional cell expansion during epidermal root hair development. Here we report that three members of the cyclic nucleotide-gated channel family are required to maintain cytosolic Ca2+ oscillations and the normal growth of root hairs. CNGC6, CNGC9 and CNGC14 were expressed in root hairs, with CNGC9 displaying the highest root hair specificity. In individual channel mutants, morphological defects including root hair swelling and branching, as well as bursting, were observed. The developmental phenotypes were amplified in the three cngc double mutant combinations. Finally, cngc6/9/14 triple mutants only developed bulging trichoblasts and could not form normal root hair protrusions because they burst after the transition to the rapid growth phase. Prior to developmental defects, single and double mutants showed increasingly disturbed patterns of Ca2+ oscillations. We conclude that CNGC6, CNGC9 and CNGC14 fulfill partially but not fully redundant functions in generating and maintaining tip-focused Ca2+ oscillations, which are fundamental for proper root hair growth and polarity. Furthermore, the results suggest that these calmodulin-binding and Ca2+-permeable channels organize a robust tip-focused oscillatory calcium gradient, which is not essential for root hair initiation but is required to control the integrity of the root hair after the transition to the rapid growth phase. Our findings also show that root hairs possess a large ability to compensate calcium-signaling defects, and add new players to the regulatory network, which coordinates cell wall properties and cell expansion during polar root hair growth.
CRIS-Team Scopus Importer:2019-09-03
Keywords: Arabidopsis thaliana; calcium channel; polar growth; R-GECO1; RootChip; trichoblast

TETRASPANINs in Plants - Reimann, Ronny; Kost, Benedikt; Dettmer, Jan (Frontiers in Plant Science, 2017)
Tetraspanins are small transmembrane proteins that laterally associate with each other and cluster with numerous partner proteins as well as lipids. These interactions result in the formation of a distinct class of membrane domains, the tetraspanin-enriched microdomains (TEMs), which influence numerous cellular processes such as cell adhesion and fusion, intracellular membrane trafficking, signaling, morphogenesis, motility as well as interaction with pathogens and cancer development. The majority of information available about tetraspanins is based on studies using animal models or cell lines, but tetraspanins are also present in fungi and plants. Recent studies indicate that tetraspanins have important functions in plant development, reproduction and stress responses. Here we provide a brief summary of the current state of tetraspanin research in plants.
Keywords: tetraspanins; Arabidopsis; rice; plant reproduction; embryogenesis; plant growth